A comparative fracture analysis on as-received and electrochemically hydrogen charged API X60 and API X60SS pipeline steels subjected to tensile testing. (November 2021) - Mohtadi-Bonab, M.A.; Masoumi, Mohammad; Szpunar, J.A.
Highlights: An analysis of fracture surfaces in X60 and X60SS steels in acidic medium is done. Fracture occurs by micro voids formation, their growth and coalescence at center. Hydrogen embrittlement in API X60 steel is more noticeable than API X60SS steel. A stepwise crack jumps with 45° from one crack traction line to another in X60 steel. The crack propagates intergranularly along gains with mismatch Taylor values. Abstract: In this study, a comparative analysis of fracture surfaces in API X60 and API X60SS pipeline steels is carried out after hydrogen charging followed by tensile testing. The JIS test setup is also utilized in order to measure the amount of discharged hydrogen through the microstructure of both steels. EBSD measurements are also done on as-received and hydrogen charged specimens in order to observed the HIC propagation. The results show that a considerable amount of hydrogen is able to diffuse through the microstructure of both steels. The tensile testing after hydrogen charging proves that hydrogen embrittlement occurs significantly in both steels. At the center of cross section in both steels, the fracture occurs by micro-voids formation, their growth and coalescence around the different types of inclusions. In charged specimens, dimples are shallower in both specimens compared with the dimples in the fracture surfaces of as-received specimens. Comparatively, hydrogen embrittlement in API X60 steel is more noticeable and its surface is more flat than the API X60SS steel. In hydrogen-charged API X60 steel, EBSD map shows a crack stepwise jumping with 45° from one crack traction line to another, with both intergranular and transgranular crack propagation mechanisms. Moreover, the crack propagates intergranularly along gains with mismatch Taylor values, while transgranular propagation mostly observed within the hard grains with high amount of dislocation density and internal energy associated with KAM map. In the case of API X60SS steel, no evidence of HIC crack was observed.